Hubungan Tingkat Pengetahuan dengan Perilaku Membaca Label Gizi pada Remaja Di SMA N 10 Kota Jambi - Salsabila, Aura Apriyunda; Wulansari, Arnati; Jeki, Andicha Gustra (3031-8572, 2024)
The level of consumer awareness of labels is still relatively low (30.3% - 34.3%), especially for highly educated consumers (2.3). Research in South Africa also showed low results (48.48%) for consumers who often or always read labels with the category of highly educated respondents. In addition, the prevalence of label use reported based on literature studies from various countries such as Lesotho (40.5%), Chile (55%), and Trinidad (58.5%) for the frequent and always categories. The habit of reading labels among adolescent consumers is still low. In addition, not all parts of the label, especially the nutritional value information, are read and understood by adolescents. Implementation of a healthier diet can be done by reading and understanding nutritional value information on product labels. The purpose of this study was to determine the relationship between the level of knowledge and the behaviour of reading nutrition labels among adolescents at SMAN 10 Jambi City. This study was conducted in April-July 2024 at SMA N 10 Jambi City. This study is a quantitative study with a cross-sectional design. Data collection by filling out a questionnaire. The population was 576 adolescents and a sample of 86 adolescents. Data analysis in this study used univariate and bivariate analysis using chi-square. The results showed a percentage description of the level of knowledge of reading nutrition labels, namely as many as 20 respondents (23.3%) were lacking, 28 respondents (32.6) were sufficient, 38 respondents (44.2%) had a level of knowledge of reading labels in the good category, 59 respondents (68.6%) had reading behaviour of nutrition labels in the sufficient category. 23 respondents. (26.7%) were poor, 4 respondents (4.7%) were good. There was no relationship between knowledge level and nutrition label reading behaviour with a p-value of 0.720. It can be concluded that most adolescents already have a good level of label reading knowledge but have poor nutrition label reading behaviour.